Pengaruh Penggunaan Protein dan Kultur Khamir Dalam Ransum Terhadap Mortalitas Embrio Ayam Arab - Natsir, Nur Alim (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Protein is an important nutrient in the diet. The availability of protein in the diet is absolutely necessary as a source of building blocks for growth, replacement of damaged tissue and maintaining reproductive functions. In the preparation of a perfect ration, the balance of energy and protein, amino acids need to be considered because they determine the productivity and reproduction of chickens. The purpose of this study was to determine the effect of the use of protein and yeast culture in the ration on the mortality of Arabic chicken embryos. The observed effects include the interaction effect and the single effect of protein level and yeast culture in the ration on the mortality of Arabic chicken embryos. The research material is as many as 240